THE IMPACT OF MARKETING STRATEGY, PRODUCT INNOVATION, AND DIGITAL LITERACY ON IMPROVING THE PERFORMANCE OF SMEs IN PALANGKARAYA CITY WITH COMPETITIVE ADVANTAGE AS A MEDIATION VARIABLE - I Made Irham Muhammad; J.E. Sutanto (International Journal of Economics, Business and Accounting Research (IJEBAR), 2026)
Most SMEs in Palangkaraya City still rely heavily on traditional marketing methods. This situation indicates that most SMEs have not yet been able to adapt to developments in modern marketing technology, resulting in limited competitiveness, low market penetration, and slow business growth compared to businesses in other regions. The objective of this study is to examine the influence of marketing strategies, product innovation, digital literacy, and competitive advantage on SME performance, as well as to determine the influence of marketing strategies, product innovation, and digital literacy on SME performance through competitive advantage as a mediating variable. This study includes a sample of 230 SMEs in Palangkaraya City across the handicrafts, food and beverages, and retail sectors. The research method used is quantitative, employing Partial Least Squares. The findings indicate that marketing strategies, product innovation, digital literacy, and competitive advantage have a significant and positive impact on SME performance; furthermore, competitive advantage mediates the relationship between marketing strategies, product innovation, and digital literacy and SME performance.